Ensured Administrative Quality of the STEM Program at Higher Education Institution - Shindi, Sanaa; Alsheikh, Ghadah (International Journal of Psychosocial Rehabilitation, 2020)
This study aims at investigating the impact of the STEM program on higher education institutions in developing the quality of pedagogical knowledge in science colleges. To answer the study questions and test its hypotheses, the researchers used a quasi-experimental design. As the work has been done to build the two study tools from a test, the quality of pedagogical knowledge and the study sample consist of 50 faculty of science, and it was divided into two groups: experimental and control. The study concluded that applying STEM programs reflects their positive impact on developing the quality of pedagogical knowledge of science programs.